A case of dentigerous cyst in a pediatric patient - With an insight into differential diagnostic entities - K.K. Deepa; Anubhav Jannu; Mithun Kulambi; H.S. Shalini (Advances in Oral and Maxillofacial Surgery, 2021)
Dentigerous cysts are one of the most common developmental odontogenic cysts involving the unerupted or impacted tooth. Most frequently seen in 20–30 years of life. Cases which have been reported within 10 years of life, in mixed dentition period are hardly few in number. Here we present an interesting case of dentigerous cyst in a pediatric patient involving unerupted permanent mandibular right second premolar with an insight into differential diagnostic entities of dentigerous cyst. Complete removal of the cyst along with attached tooth structure was done under general anesthesia. Careful evaluation of the patient with past medical history, clinical, radiographic and histopathological examination would help the clinician in early diagnosis to administer appropriate treatment.